Two-chamber gasifier cook stove - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
We have finalized standard boiling tests and emission measurements of the gasifier cook stove in 2017 to quantify savings in firewood consumption and offsets in emissions as compared to commonly used incineration systems (three-stone fire).